Analisis Keunggulan Produk Kerajinan Rambut di Desa Karang Banjar Kecamatan Bojongsari, Purbalingga, 2007 (Pendekatan Revealed Comparative Advantage (RCA) dan Sustainable Competitive Advantage (SCA)) - Agus Arifin (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
This research was aimed to evaluate the advantage of hair production in Karangbanjar village, Bojongsari, Purbalingga, Central Java, wherefore this product has the mainly advantage in Purbalingga regency. The analysis object is small enterprises in the hair production centre which is the traditional hair product located in Karangbanjar village. The product advantage was analyzed through comparative and competitive advantages approaches. The research tools are Revealed Comparative Advantage (RCA) to analyze comparative advantage and Sustainable Competitive Advantage (SCA) to study competitive advantage. The results obtained from this research are based on product advantage analysis, small enterprises of hair production exactly have comparative and competitive advantages. Key words: comparative advantage, competitive advantage, hair production